Operations management model based on mixed methodologies to increase production efficiency in a retail laundry - Cupe Escalante, Fiorella Nicol (2024)
Currently, the textile sector significantly impacts the country’s economy in terms of its contribution to the GDP and the economi cally active population. Because of that, the problems that affect this sector have significant consequences for the rest of the people and the nation. Furthermore, in addition, the national and international competitiveness of the market forces companies to improve their processes and productivity at a fast pace. In this context, MSEs and SMEs,fromwhichalargepartoftheeconomicallyactivepopulation originates, must be included in the search for increased productivity and efficiency in their processes. This Study aims to evidence how the use of mixed engineering tools will solve the problems above by improving the efficiency of production in operations of an SME Laundry from the textile sector. The improvement model proposed is based on TPM (autonomous maintenance, Planned maintenance), MRP, and Standardized work. In addition, The software ARENA simulator validated the results in the whole process observed in the study case. Eventually, the implementation obtained positive results, production efficiency increased by 13%, a decrease of 30% in the Stock out rate, and MTBF improved by 26.73% compared to the previous situation.